Clube dos valentes: prevenção da violência e desenvolvimento de amizade na educação infantil - Galli, Ernesto Ferreira (2020)
This doctoral thesis aims to understand what is the impact of preventive socialization on egalitarian models of masculinity, in opposition to violent actions, based on the dialogical practices of the “Clube de Valentes” and on the valorization of solidarity and friendship. This study aims to provide elements to think about the prevention of violence against women from the practice of Brave Club - practice is aimed at rejecting violence through strengthening friendships. To achieve this goal, it was proposed to analyze in a child education class with which the Brave Club in Brazil develops, the changes that have occurred in boys as to their behaviors, observing those that come closest to alternative masculinity, as well as the transformations occurred in the girls understanding of who the brave boys are and who is worth being friends with. As specific objectives we had in the study: to understand in which masculinity model the boys of the class are initially being socialized; analyze the interactions and behaviors that occur in the class and that are transformative socializations, that lead to equality, friendship and solidarity, and those that exclude, that humiliate and subject girls and boys to someone; to analyze together with the teacher and the children, what transforming elements were made possible through the club of the brave in the preventive socialization of gender violence and that promoted the valorization of models of egalitarian masculinities in the studied context. Based on these objectives, a room for early childhood education with 5-year-olds was analyzed the only room that hosts the Brave Club in Brazil. To carry out the data collection and analysis, the communicative methodology was used, which has as premise the dialogue between all involved in the research, as well as analyzing the elements that prevent the transformation - excluding - and the elements that promote the transformation - transformers. Based on this methodology, communicative groups were interviewed and communicated with communicative life with family and teacher, and communicative observations of the class. The data were triangulated and organized into categories: socializing in the room, brave club, good friendships, conflict resolution and masculinity. Data analysis indicated that the exclusionary dimensions were: isolation from practice at school, lack of boys, socialization of boys, models, and categorization of children. The transformers were: teacher training, denouncing the model based on violence, conflict / dialogue resolution, good friendships and participatory family members. Considering these elements, it was possible to visualize the impact of the brave club on the lives of children, promoting a more egalitarian model of masculinity among boys, as it started to value equality, respect and solidarity in relationships between friends. And the girls changed their perception of what characteristics they value in good friendships. Therefore, socialization for prevention was promoted, since violence and aggression started to be no longer admired as elements of masculinity.